2013
DOI: 10.1111/idj.12055
|View full text |Cite
|
Sign up to set email alerts
|

The care of the primary dentition by general dental practitioners and paediatric dentists

Abstract: GDPs and PDs have different dental care approach patterns for pre-school children with dental caries. Wide variation in the views about the best way to treat the child exists within both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 20 publications
3
26
1
1
Order By: Relevance
“…Randomised clinical trials are rare in paediatric dentistry and this hampers evidencebased discussions about the best way to treat children (Tickle et al 2007). The present findings of different approach patterns for pre-school children with dental caries are consistent with similar studies among GDPs and PDs in UK and Hong Kong (Duggal 2006;Lee et al 2013).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Randomised clinical trials are rare in paediatric dentistry and this hampers evidencebased discussions about the best way to treat children (Tickle et al 2007). The present findings of different approach patterns for pre-school children with dental caries are consistent with similar studies among GDPs and PDs in UK and Hong Kong (Duggal 2006;Lee et al 2013).…”
Section: Discussionsupporting
confidence: 91%
“…Two common clinical situations showing five-year-old children with severe caries in primary teeth (Tables 1 & 2 and Figs. 1 & 2) were presented to general practitioners (GDPs) employed in the Public Dental Service (PDS) in Norway and PDs as well as specializing dentists. The response rate for GDPs (65 %) was comparable with that in other surveys (Tickle et al 2007;Hill et al 2008;Shelley et al 2012;Brahm et al 2013;Lee et al 2013). The respondents accounted for about one-third of all public dental officers in Norway.…”
Section: Discussionsupporting
confidence: 76%
“…Neste estudo, foram avaliadas 59 crianças na idade entre 5 e 10 anos, a variável idade da criança não apresentou associação significativa com a variável dependente do estudo, a necessidade de reparo das restaurações (p < 0,202). Provavelmente, se o estudo fosse realizado com uma amostra de crianças de menor idade, a associação seria mais facilmente verificada, como citada por outros autores 16,17 .…”
Section: Materiais E Métodounclassified
“…Because of the characteristics of ART, this technique has become an option among these practitioners. A cross-sectional survey of general dentists conducted in Hong Kong reported that ART was the preferred treatment option for a hypothetical 4-year-old healthy and cooperative boy, whereas pediatric dentists favored conventional restorative treatment for the same patient [12]. A second cross-sectional survey conducted in England reported similar results where ART was the preferred method among the general dental practitioners to restore a primary molar with a proximal lesion in a six-year-old boy [13].…”
Section: Introductionmentioning
confidence: 96%